2009
DOI: 10.1111/j.1439-0426.2009.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of middle Mississippi River shovelnose sturgeon: insights from seasonal and age variation in plasma sex steroid and calcium concentrations

Abstract: Additional research is needed to elucidate fall spawning by shovelnose sturgeon in the MMR.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…Variations in several blood parameters have been reported to be characteristic of pre‐spawning and spawning periods, and significantly different levels were found among sex and maturity stages. A physiological increase in plasma Mg ++ concentration, as observed in this study, was reported for example as a function of vitellogenesis in A. transmontanus , A. persicus and Scaphirhynchus platarynchus (Linares‐Casenave et al., 2003; Asadi et al., 2006b; Stahl et al., 2009). Similarly, an increase in plasma albumin concentration may be linked to increased steroid hormone transportation (Shahsavani et al., 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Variations in several blood parameters have been reported to be characteristic of pre‐spawning and spawning periods, and significantly different levels were found among sex and maturity stages. A physiological increase in plasma Mg ++ concentration, as observed in this study, was reported for example as a function of vitellogenesis in A. transmontanus , A. persicus and Scaphirhynchus platarynchus (Linares‐Casenave et al., 2003; Asadi et al., 2006b; Stahl et al., 2009). Similarly, an increase in plasma albumin concentration may be linked to increased steroid hormone transportation (Shahsavani et al., 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Coincident with these changes in [Ca 2+ ] were declines in circulating [K + ] and [Na + ], which were resolved by day 7. Plasma [Ca 2+ ] is known to be associated with vitellogenesis and can be used as a predictor of reproductive status in the Acipenserid species examined to date (Van Eenennaam et al., ; Linares‐Casenave et al., ; Stahl et al., ). Thus, the observed increase in [Ca 2+ ] is likely related to reproductive status, and furthermore the concentration measured is in accord with plasma [Ca 2+ ] during spawning in other Acipenser species (McEnroe and Cech, ; Williot et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of ovarian follicles achieving ovulatory competence could therefore be used effectively to estimate the timing of hormonal treatment by evaluating follicular maturity. Some species such as white sturgeon and shovelnose sturgeon ( Scaphirhynchus platorynchus ) may also spawn in autumn (Conte et al., ; Stahl et al., ). In fact, peaks in plasma estradiol‐17β, Ca 2+ and testosterone in shovelnose sturgeon were observed not only in April but also in autumn (Stahl et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Some species such as white sturgeon and shovelnose sturgeon ( Scaphirhynchus platorynchus ) may also spawn in autumn (Conte et al., ; Stahl et al., ). In fact, peaks in plasma estradiol‐17β, Ca 2+ and testosterone in shovelnose sturgeon were observed not only in April but also in autumn (Stahl et al., ). The ratio of follicles that acquired ovulatory competence first increased in November or January; thus, eggs may be collected during those months.…”
Section: Discussionmentioning
confidence: 99%